Mechanism of Delaying Cartilage Degeneration in Knee Osteoarthritis with Rongjin Niantong Recipe Based on lncRNA NEAT1 and Nrf2/ARE Pathway - FU Changlong; XIE Xinyu; QIU Zhiwei; HUANG Yanfeng; JIN Linglu; LI Xihai (康复学报)
ObjectiveTo evaluate the effect of Rongjin Niantong Recipe on knee osteoarthritis model rats, and to explore the mechanism of delaying cartilage degeneration in knee osteoarthritis based on long noncoding RNA (lncRNA) NEAT1 and Nrf2/ARE pathway.MethodsAfter adaptive feeding for one week, a total of 45 SPF SD rats aged two months were randomly divided into blank group and sodium iodoacetate group, with 15,30 cases in each group. Under anesthesia, 0.05 mL sodium iodoacetate at a concentration of 20 mg/mL was injected into the right knee joint to establish the knee osteoarthritis model, and the blank group was injected with the same amount of normal saline. After modeling was assessed to be successful, the sodium iodoacetate group were randomly divided into model group and Rongjin Niantong Recipe group, with 15 cases in each group. The Rongjin Niantong Recipe group were given 1.9 g/(kg·d) the medicine by gavage, and the blank group and the model group were given the same amount of normal saline by gavage for eight weeks. After the intervention, all groups were sacrificed under anesthesia, and the right knee tissues were separated and collected; HE staining was used to observe the pathological changes; Western blot was used to detect the expression levels of Nrf2, heme oxygenase-1 (HO-1), NAD (P) H quinone oxidoreductase-1 (NQO-1), kelch like ECH-associated protein 1 (Keap1) and inducible nitric oxide synthase (iNOS) in cartilage; Real-time PCR was used to detect the expression of lncRNA NEAT1 in cartilage tissue.Results1) Pathological changes of cartilage tissue: the cartilage matrix was light red and uniform, with complete tissue structure and clear tissue margins of each layer in the blank group; in the model group, the chondrocytes grew in clusters with thinner tangent layer. The surface layer was destroyed and the transitional layer and the radiation layer became disordered and partial calcified. There were obvious calcifications in the calcified layer. In addition, the adhesion line between the calcified layer and the subchondral bone fluctuated greatly and was discontinuous. The tangents of the superficial layer in the Rongjin Niantong Recipe group were completed and basically paralleled to the articular surface, and the transitional layer, radiation layer, calcification layer and other layers were relatively clear. 2) Expressions of Nrf2/ARE pathway related proteins in the cartilage: compared with the blank group, the protein expression levels of Keap1 and iNOS of the model group significantly increased (P<0.05) and the protein expression levels of Nrf2, HO-1 and NQO-1 significantly decreased (P<0.05). Compared with the model group, the protein expression levels of Keap1 and iNOS in the Rongjin Niantong Recipe group significantly decreased (P<0.05), while the protein expression levels of Nrf2, HO-1 and NQO-1 significantly increased (P<0.05). 3) Expressions of lncRNA NEAT1 in cartilage: compared with the blank group, the expression level of lncRNA NEAT1 in the model group was significantly higher (P<0.05); compared with the model group, the expression level of lncRNA NEAT1 in the Rongjin Niantong Recipe group significantly decreased (P<0.05).ConclusionRongjin Niantong Recipe can delay cartilage degeneration in rats with osteoarthritis. The mechanism may be related to the down-regulation of lncRNA NEAT1 level, up-regulation of Nrf2 signal and antioxidant signal molecules expressions, and down-regulation of pro-oxidation signal molecules and inhibition of oxidative stress level.